War, Inflation, Monetary Reform and the Art Market - Geraldine David; Kim Oosterlinck (European Historical Economics Society (EHES), 2012)
During World War II, the art market experienced a massive boom in occupied countries. The discretion, the inflation proof character, the absence of market intervention and the possibility to resell artworks abroad have been suggested to explain why investing in artworks was one of the most interesting opportunities under the German boot. On basis of an original database of close to 4000 artworks sold between 1944 and 1951 at Giroux, one of the most important Art Gallery in Brussels, this paper analyzes, the price movements on the Belgian art market following the liberation. Market reactions following the war are used to understand which motivations played the most important role in investors' decisions. Prices on the art market experienced a massive drop. This huge price decline is attributed to two elements: fear of prosecution for war profits and the monetary reforms set into place in October 1944.
Keywords: N14; N44; Z11; 330; Art market; Art Investment; WWII; Belgium; Post-war; Monetary reforms